1994
DOI: 10.1002/jab.770050205
|View full text |Cite
|
Sign up to set email alerts
|

Materials and design concepts for an intervertebral disc spacer. I. Fiber‐reinforced composite design

Abstract: The intervertebral disc is a complex joint anatomically and functionally. It may be displaced or damaged due to trauma or a disease process. To alleviate this condition, it may be necessary to remove the involved disc surgically and fuse the two adjacent vertebrae. Fusion is one option; however, replacing the damaged disc (or part thereof) with a suitable synthetic equivalent to allow near normal joint motion is more desirable. Unfortunately, the complex mechanical properties of the lumbar disc cannot be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 14 publications
(2 reference statements)
1
12
0
Order By: Relevance
“…One previous report of a hydrogel type nucleus prosthesis tested in human cadavers and implanted via an experimental annulus sparing technique had similar axial stiffness to that in the present study [42]. Another prosthetic (total) disc which is non-articulating and made of fiber reinforced polymers also had an axial compressive stiffness that was similar to the device described in the current study [39]. …”
Section: Discussionsupporting
confidence: 81%
“…One previous report of a hydrogel type nucleus prosthesis tested in human cadavers and implanted via an experimental annulus sparing technique had similar axial stiffness to that in the present study [42]. Another prosthetic (total) disc which is non-articulating and made of fiber reinforced polymers also had an axial compressive stiffness that was similar to the device described in the current study [39]. …”
Section: Discussionsupporting
confidence: 81%
“…109 Operative fusion (arthrodesis) involves placement of a bone graft within the disc space post-discectomy, with further stabilization of the joint attained using spinal instrumentation. 110 A study from The Healthcare Cost and Utilization Project 111 reported that 297,883 spinal fusions were performed in the United States in 2003. Interbody fusion has resulted in successful clinical outcomes and succeeds in alleviating pain by removing the disc and eliminating any motion through the joint.…”
Section: Interbody Fusionmentioning
confidence: 99%
“…To this end, the device should allow normal, unconstrained physiologic motions; permitting the spine to regulate the device, as opposed to spinal motion adapting to the implant. Additionally, the device must adequately address the in vivo loading conditions [17,18,21,22,23,24,30], must function as a stand-alone implant in the presence of an intact posterior column, and must resist wear, cold flow and material delamination. Most importantly and most challenging is for the device to encourage osseointegration at the bone-metal interface while preserving the biomechanical properties of motion.…”
Section: Discussionmentioning
confidence: 99%